Julie and Julia : my year of cooking dangerously - Powell, Julie, 1973-2022 (Back Bay Books, 2006)
Recounts how the author escaped the doldrums of an unpromising career and lackluster Queens apartment by mastering every recipe in Julia Child's 1961 classic, Mastering the Art of French Cooking, a year-long endeavor of humor and accomplishment that transformed her life. Reader's Guide included.